OS PRINCÍPIOS DE CONSTITUIÇÃO DE UMA REALEZA SAGRADA SOB O GOVERNO DE CONSTÂNCIO II (337-361) - da Silva, Gilvan Ventura (PHOÎNIX, 2020)
This article intends to discuss the constitution of a divine kingship during the reign of Constantius II. In order to do it we analyze the relationship between religion and politics in the Roman Empire and, afterwards, we discuss the anthropological concept of "divine kingship ". Finally, we consider the possibility of comprehending Constantius ' monarchy as a particular kind of divine kingship in the Later Roman Empire.